Oxidative Stress in Polycystic Ovarian Syndrome and the Effect of Antioxidant N-Acetylcysteine on Ovulation and Pregnancy Rate - (:unkn) unknown (CUREUS INC, 2021)
Polycystic ovarian syndrome (PCOS) is an endocrinological condition that leads to infertility in many females. N-acetylcysteine (NAC), a novel antioxidant, is being used as an adjuvant to treat infertility in females suffering from PCOS. This review aims to evaluate oxidative stress in females suffering from PCOS and assess whether the anti-oxidizing properties of NAC are beneficial in enhancing the rate of ovulation and pregnancy in infertile PCOS females. A literature search was conducted manually on PubMed and Google Scholar databases using the following keywords: N-Acetylcysteine, PCOS, Oxidative stress, Antioxidants, and infertility alone and/or in combination for data collection. The studies were manually screened and, after applying inclusion-exclusion criteria, 32 studies consisting of 2466 females of the reproductive age group are included in this review. Our review revealed that females suffering from PCOS tend to show elevated levels of inflammatory markers and a decrease in antioxidant capacity. When used in combination with clomiphene citrate or letrozole, NAC increases ovulation and pregnancy rate in infertile females suffering from PCOS and positively affects the quality of oocytes and number of follicles >= 18mm. Moreover, its side effect profile is low. It also results in a mild increase in endometrial thickness in some females. Future studies on a large sample size using NAC alone are highly recommended to evaluate its role as a single-drug therapy for treating infertility in females suffering from PCOS.
Keywords: n-acetylcysteine; pcos; oxidative stress; antioxidants; infertility; CLOMIPHENE CITRATE; METFORMIN; ADJUVANT; INDUCTION; IMPROVES; GROWTH; OOCYTE; WOMEN; PCOS